Patient Centered Medicine - Sayligil, Omur (IntechOpen, 2017)
Patient-centered medicine is not an illness-centered, a physician-centered, or a hospital-centered medicine approach. In this book, it is aimed at presenting an approach to patient-centered medicine from the beginning of life to the end of life. As indicated by W. Osler, "It is much more important to know what sort of a patient has a disease than what sort of a disease a patient has." In our day, if the physicians and healthcare professionals could consider more than the diseased organ and provide healthcare by comforting the patients by respecting their values, beliefs, needs, and preferences; informing them and their relatives at every stage; and comforting the patients physically by controlling the pain and relieving their worries and fears, patients obeying the rules of physicians would become patients with high adaptation and participation to the treatment.